Systematic analysis of control panel interfaces using formal tools - Campos, José C. (2008)
The paper explores the role that formal modeling may play in aiding the visualization and implementation of usability requirements of a control panel. We propose that this form of analysis should become a systematic and routine aspect of the development Of Such interfaces. We use a notation for describing the interface that is convenient to use by software engineers, and describe a set of tools designed to make the process systematic and exhaustive.